Konstruksi Pernikahan Beda Agama Perspektif Hermeneutika Hans-George Gadamer (Perempuan Muslimah Menikah dengan Laki-laki Ahl al-Kitab) - Muhyidin Muhyidin; Nashihin Nashihin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The discourse on the prohibition of interfaith marriage, in this case Muslim women with ahl al-kitab men, will still be interesting to study. The majority of scholars forbade it, under the rational pretext that women are psychologically weak, so it is feared that she will be influenced and follow the husband's religion. This is in contrast to Muslim men marrying women of ahlu al-kitab, which the majority of scholars allow, on the basis of the text of the Qur'an Surah al-Maidah Verse 5, also by basing themselves on the logical pretext that men are more dominant, so as to be able to influence their wives to embrace Islam, or at least the husband is very unlikely to be influenced by his wife's religion. In this context, using Hans-Georg Gadamer's hermeneutic approach, the author concludes that the prohibition of Muslim women marrying ahlu al-Kitab men is not absolute, meaning that under certain conditions if it is considered that the Muslim woman has more capacity than the man, then of course this is allowed. Even using this approach, muslim men can be barred from marrying ahlu al-Kitab women, if it is strongly suspected that muslim women are more dominant.